Hi guys! How do we find the normal to the curve in this problem?

**Find the equations of the tangent to the curve y = x - x[SUP]3[/SUP] at (1,0), and the normal to the same curve at (1/2, 3/8). Find where the tangent and normal intersect.**

First I found the derivative and then calculated the gradient of the tangent. After it, I determined the equation of the tangent:

y = x- x[SUP]3[/SUP]

dy/dx = 1 - 3x[SUP]2[/SUP] >>>>>(1,0)

m = 1 - 3 = -2

y - y[SUB]0[/SUB] = m.(x - x[SUB]0[/SUB])

y - 0 = -2.(x - 1)

y = -2x + 2

Normally, I would do that:

The normal to the curve = -1/m

= -1/-2

= 1/2

But I know it's false and "the normal to the same curve at (1/2, 3/8)" makes me confused. Do I need to find the slope of the tangent at that point to find the normal? Like :

m = 1 - 3x[SUP]2[/SUP] >>>>>>(1/2, 3/8)

m = 1 - 3.(1/2)[SUP]2[/SUP]

m = 1/4

the normal = -1/m

= -1/1/4

= -4

y - y[SUB]0[/SUB] = m.(x - x[SUB]0[/SUB]) >>>>>>>(1/2, 3/8)

y - 3/8 = -4.(x - 1/2)

y = -4x + 19/8

??

Any help would be appreciated.

**Find the equations of the tangent to the curve y = x - x[SUP]3[/SUP] at (1,0), and the normal to the same curve at (1/2, 3/8). Find where the tangent and normal intersect.**

First I found the derivative and then calculated the gradient of the tangent. After it, I determined the equation of the tangent:

y = x- x[SUP]3[/SUP]

dy/dx = 1 - 3x[SUP]2[/SUP] >>>>>(1,0)

m = 1 - 3 = -2

y - y[SUB]0[/SUB] = m.(x - x[SUB]0[/SUB])

y - 0 = -2.(x - 1)

y = -2x + 2

Normally, I would do that:

The normal to the curve = -1/m

= -1/-2

= 1/2

But I know it's false and "the normal to the same curve at (1/2, 3/8)" makes me confused. Do I need to find the slope of the tangent at that point to find the normal? Like :

m = 1 - 3x[SUP]2[/SUP] >>>>>>(1/2, 3/8)

m = 1 - 3.(1/2)[SUP]2[/SUP]

m = 1/4

the normal = -1/m

= -1/1/4

= -4

y - y[SUB]0[/SUB] = m.(x - x[SUB]0[/SUB]) >>>>>>>(1/2, 3/8)

y - 3/8 = -4.(x - 1/2)

y = -4x + 19/8

??

Any help would be appreciated.

Last edited: